The Effect of Hatha Yoga on Dysmenorrhea Intensity among Adolescent Girls: A Pilot Study - Indana Rizki Navid; Ilmiatus Qoyimah; Moh. Ubaidillah Faqih; Tiara Putri Ryandini (PT Pubsains Nur Cendekia, 2026)
Background: Dysmenorrhea is one of the most common reproductive health problems among adolescent girls, characterized by lower abdominal pain or cramping during menstruation, often accompanied by symptoms such as nausea, dizziness, and fatigue. This condition can significantly impact adolescents' quality of life by impairing academic concentration, disrupting sleep patterns, limiting daily activities, and increasing school absenteeism. Aims: To determine the effect of Hatha Yoga on the intensity of primary dysmenorrhea among adolescent girls. Methods: A pilot study using a one-group pretest–posttest design was conducted involving 30 eighth-grade female students selected through purposive sampling. Dysmenorrhea intensity was assessed using the Numeric Rating Scale (NRS). Participants received a structured Hatha Yoga intervention consisting of 12 sessions over six weeks, with two sessions per week. Data were analyzed using the Wilcoxon Signed-Ranks Test. Results: The analysis showed a statistically significant reduction in dysmenorrhea intensity following the intervention (Z = −2.828; p = 0.005). Conclusions: Hatha Yoga was associated with a significant reduction in dysmenorrhea intensity; however, the absence of a control group limits causal inferenc.